KINERJA PT. BANK SYARIAH XYZ CABANG DEPOK MENGGUNAKAN BALANCED SCORECARD - Budi Rahardjo (Faculty of Economic and Business, University of Pasundan, 2020)
The growth and development of Islamic banking in Indonesia brings an atmosphere of competition in the banking business discourse. PT Bank syariah XYZ is one of the largest sharia banks that always try to provide the best service to their customers in a professional manner. In the midst of fierce competition, PT Bank Syariah XYZ is currently experiencing a setback in performance marked by increasing NPF. The results obtained from performance measurements using the Balanced Scorecard approach to determine the size of the results of each target as a tangible measure, namely the size of the results indicated by an increase in revenue and a decrease in NPF PT Bank Syariah XYZ Depok Branch, customer satisfaction index, increase in the number of accounts, increasing the number of excellent services, efficiency of Teller and CS queues with customers, increasing the number of ATM machines and transaction time efficiency, increasing the quality and competence of employees, reliability of technology and information as well as increasing employee satisfaction and motivation.